Implementation of Delegation of Authority from District to Camat in Public Services at Way Kanan District Lampung Province - Arie Anthony Thamrin; Muchlis Hamdi; Djohermansyah Djohan; Megandaru W. Kawuryan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The delegation of authority from the Regent of Way Kanan to the sub-district head is a pattern of delegation of government authority which forms the basis for the implementation of roles and responsibilities as well as the implementation of the duties and functions of the sub-district office. With the delegation of authority, the camat can certainly optimize its role as the front line of public services. The Regent's political desire to delegate some of his authority in the context of accelerating services to the community, secondly the Regent's political will to make the sub-district a community service center, the third is the logoowa of regional technical institutions to delegate technical authority that can be carried out by the Camat in implementing various government policies and activities so as to increase satisfaction. public services in the community. This study uses a qualitative method with a phenomenological approach. The results showed that, aspects of the procedures in the appointment of Way Kanan, Way Kanan Regency, Lampung Province, had tried to support the placement of Way Kanan according to the technical science of government in carrying out its main tasks and functions, but not yet fully due to limited human resources in Way Kanan Regency. . The implementation of the delegation of authority from the Regent to the Camat in Way Kanan Regency, Lampung Province as well as the implementation of the authority of the Camat in Way Right Regency has not been carried out effectively because it does not yet have an accommodatively regulated authority limit.